Accounting Data Encryption Processing Based on Data Encryption Standard Algorithm. (4th June 2021) - Chen, Meixi
Abstract : With the application of computer and network technology in the field of accounting, the development of accounting informationization is an inevitable trend, and the construction of accounting statement data into the data warehouse will be the basis of intelligent decision-making. The complexity of industry accounting statements and the arbitrariness and diversity of users' needs for obtaining information using statements limit the development, popularization, and application of industry accounting statements. As a block encryption algorithm, the Data Encryption Standard (DES) algorithm uses 64-bit packet data for encryption and decryption. Each eighth bit of the key is used as a parity bit; that is, the actual key length is 56 bits. Encryption and decryption use the same algorithm structure, but the order in which the subkeys are used is reversed. Under the control of the subkey, inputting 64-bit plaintext can produce 64-bit ciphertext output; otherwise, inputting 64-bit ciphertext can produce 64-bit plaintext output. The confidentiality of the DES algorithm depends on the key, and only a very small number of keys are considered weak keys, which can be easily avoided in practical applications. The 3DES algorithm is a cascade of the DES algorithm, and its encryption process is based on the DES algorithm principle. This article explains the encryption process of the DES algorithm and introduces the composition of the 3DES algorithm. The experimental results show that the 3DES encryption algorithm still has a better encryption effect and "avalanche effect" than before the improvement. In addition, for the 3DES algorithm, its encryption efficiency has not been greatly affected. The 3DES encryption algorithm achieves one encryption process at a time to some extent, can effectively resist exhaustive search attacks, and enhance the security of the DES algorithm.